Implementação das placas de Kirchhoff e de Mindlin utilizando o método dos elementos finitos - Menezes, Tarik de Sousa (2017)
Describes the procedure of implementing a computer program for analysis of thin and thick plates with lateral loading. Highlights the assumptions for the formulation of the governing differential equations. It lists the steps to obtain the stiffness matrices and the vectors of equivalent nodal forces. It uses the theory of elasticity to obtain the relations between displacements, strains and stresses. Describes isoparametric elements and defines their shape functions. Describes the Gauss quadrature procedure for numerical integration